Diseño de una máquina para el laboratorio de tratamientos térmicos de la Fundación Universidad de América que cuantifique y verifique las variables para una correcta realización del ensayo Jominy bajo la norma ASTM-A255 (2022)
Heat treatments are controlled processes that are used to modify the mechanical properties of components according to the needs of operation.These processes involve various factors such as the type of material, temperature, cooling rate and time exposed to treatment. In this context, this document consolidates a proposal to contribute to the study of thermal treatments at the Fundación Universidad de América. Currently at the university, hardenability tests are carried out with some steels by increasing the temperature, but there is no equipment to carry out processes with controlled cooling rates. With the design of the Jominy testing machine, it is intended to consolidate a controlled process in order to obtain more precise analyses. The equipment will be governed by the ASTM A225 standard that specifies the requirements to perform a hardenability test.